A Speculative Tectonic Model for the Evolution of NW Himalaya and Karakoram - Jan, M. Qasim; Khan, Muhammad Asif (Journal of Himalayan Earth Sciences, 1981)
The Himalayas are commonly considered to be the product of collision between the Asiatic and Indo-Pakistan plates. A number of plate tectonic model have recently been proposed for the NW Himalayas. Tahirkheli et al. (1979), Kootwijk et al. (1979), and Virdi (1981) suggested the formation of Kohistan-Ladakh island arc between the two plates. Coward et al. (in press, 1982) found that the structure of the Kohistan zone is much complex for such a simple interpretation. Complicated models, involving north- and south-facing subduction zones have been envisaged by Andrews-Speed and Brookfield (1982) and Windley (pas. comm.).